Fixed-Dose Combination Therapy for the Prevention of Cardiovascular Diseases in CKD: An Individual Participant Data Meta-Analysis. - Sepanlou, Sadaf G.; Mann, Johannes; Joseph, Philip; Pais, Prem; Gao, Peggy; Sharafkhah, Maryam; Roshandel, Gholamreza; Yusuf, Salim; Malekzadeh, Reza (Clinical Journal of the American Society of Nephrology, 2023)
BACKGROUND: Fixed-dose combination treatments reduce cardiovascular disease in primary prevention. We aim to explore whether those benefits differ in the presence of CKD. METHODS: We conducted an individual participant data meta-analysis in 18,162 participants on the efficacy and safety of treatment for the primary prevention of cardiovascular disease. Combination therapies consisted of at least two BP-lowering drugs and a statin, with or without aspirin versus placebo or minimal care. Here, we examine the differential effect of fixed-dose combination treatment on the risk of developing cardiovascular disease in participants with a low eGFR (<60 ml/min per 1.73 m 2 ; Chronic Kidney Disease Epidemiology Collaboration formula) compared with a normal eGFR (≥60 ml/min per 1.73 m 2 ). The primary composite outcome was time to first occurrence of a combination of cardiovascular death, myocardial infarction, stroke, or arterial revascularization. RESULTS: At baseline, the mean level of eGFR was 76 ml/min per 1.73 m 2 (SD 17). In total, 3315 (18%) participants had low eGFR at baseline. During a median follow-up of 5 years, among participants with normal eGFR, the primary outcome occurred in 232 (3%) participants in the treatment group compared with 339 (5%) in the control group (hazard ratio, 0.68; 95% confidence interval, 0.57 to 0.81; P < 0.001). In participants with low eGFR, the primary outcome occurred in 64 (4%) participants in the treatment group compared with 130 (8%) in the control group (hazard ratio, 0.49; 95% confidence interval, 0.36 to 0.66; P < 0.001; P for interaction 0.047). The relative risk reduction among participants with low eGFR was larger for combination strategies, including aspirin compared with treatments without aspirin. Apart from dizziness, other side effects did not differ between treatment and control groups, regardless of the stage of their kidney function. CONCLUSIONS: A fixed-dose combination treatment strategy is effective and safe at preventing cardiovascular disease, irrespective of eGFR, but relative and absolute risk reductions are larger in individuals with low eGFR. PODCAST: This article contains a podcast at https://dts.podtrac.com/redirect.mp3/www.asn-online.org/media/podcast/CJASN/2023_11_08_CJN0000000000000251.mp3.
EVALuna2:586769